2020
DOI: 10.1080/22221751.2020.1785333
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel fungal species and pathogens on bat carcasses in a cave in Yunnan Province, China

Abstract: Virulent infectious fungal diseases, in natural and managed landscapes, are increasing. Fungal diseases in humans, animals and plants have caused die-off and extinction events and have become a threat to food security. A caving expedition in Yunnan Province, China, revealed two bat carcasses covered in fungal mycelia. Eleven fungal isolates were obtained from these bat carcasses, and morphological observations and multigene phylogenetic analyses revealed they were Fusarium incarnatum, Mucor hiemalis and Tricho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Our results reflect those from previous fungal studies from cave ecosystems as Ascomycota fungi usually dominate the fungal composition of cave ecosystems, followed by Basidiomycota, Zygomycota, and then others (Vanderwolf et al 2013). Four species of fungi were discovered from cave samples for the first time in this study, namely A. nitens, Ganoderma australe, Pyrrhoderma noxium, and Xylaria feejeensis (Vanderwolf et al 2013;Nováková et al 2018;Karunarathna et al 2020;Zhang et al 2020;Cunha et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Our results reflect those from previous fungal studies from cave ecosystems as Ascomycota fungi usually dominate the fungal composition of cave ecosystems, followed by Basidiomycota, Zygomycota, and then others (Vanderwolf et al 2013). Four species of fungi were discovered from cave samples for the first time in this study, namely A. nitens, Ganoderma australe, Pyrrhoderma noxium, and Xylaria feejeensis (Vanderwolf et al 2013;Nováková et al 2018;Karunarathna et al 2020;Zhang et al 2020;Cunha et al 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Yunnan Province, China, as part of the GMS, is home to an extremely wide variety of ecosystems. Mycologists working in Yunnan have recently focused their attention on abundant “less-researched habitats” for fungal occurrences, including caves, forests, grasslands, lakes, karst landscapes and mountains; accordingly, there is a rich body of literature documenting novel discoveries across the region [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Filobasidium magnum is a psychrophilic fungus; therefore, this is why it probably dominated at the lower incubation temperature [71]. In turn, the fungi of the Mucor genus were previously isolated from bat cadavers (Rhinolophus affinis) in a cave in China, and those studies indicated M. hiemalis as a dominant species [31], as well as from bat cadavers (Myotis capaccini, Myotis sp., Miniopterus schreibersii, Pipistrellus sp., and an undetermined bat) in Palummaro Cave in Italy [64]. Mucor is another widespread filamentous fungus that is found in soil and decaying plant matter.…”
Section: Fungal Species Composition and The Number Of Batsmentioning
confidence: 99%
“…The virulence of Pd is also due its preference for nitrogenous substrates occurring in bat skin and lipids [28]. Organic debris such as bat guano, plant material, and animal carcasses and wastes are crucial substrates for the development and growth of underground fungi [29][30][31]. Moreover, many microorganisms, as well as other artifacts such as cellular fragments, fungal spores, or various mycotoxins and enzymes, can be found in an aerosol form [32].…”
Section: Introductionmentioning
confidence: 99%